Characterization of a virulence-modifying protein of Leptospira interrogans identified by shotgun phage display - Lauretti-Ferreira, Fabiana; Teixeira, André Azevedo Reis; Giordano, Ricardo José; da Silva, Josefa Bezerra; Abreu, Patricia Antonia Estima; Barbosa, Angela Silva; Akamatsu, Milena Apetito; Ho, Paulo Lee (Frontiers in Microbiology, 2022)
Pathogenic species of Leptospira are etiologic agents of leptospirosis, an emerging zoonotic disease of worldwide extent and endemic in tropical regions. The growing number of identified leptospiral species sheds light to their genetic diversity and unique virulence mechanisms, many of them still remain unknown. Toxins and adhesins are important virulence factors in several pathogens, constituting promising antigens for the development of vaccines with cross-protection and long-lasting effect against leptospirosis. For this aim, we used the shotgun phage display technique to unravel new proteins with adhesive properties. A shotgun library was constructed using fragmented genomic DNA from L. interrogans serovar Copenhageni strain Fiocruz L1-130 and pG8SAET phagemid vector. Selection of phages bearing new possible cell binding antigens was performed against VERO cells, using BRASIL biopanning methodology. Analysis of selected clones revealed the hypothetical protein LIC10778, a potential exposed virulence factor that belongs to the virulence-modifying (VM) protein family (PF07598), composed of 13 members in the leptospiral strain Fiocruz L1-130. Prediction of LIC10778 tertiary structure indicates that the protein contains a cellular binding domain (N-terminal portion) and an unknown domain of no assigned activity (C-terminal portion). The predicted N-terminal domain shared structural similarities with the cell binding and internalization domain of toxins like Ricin and Abrin, as well as to the Community-Acquired Respiratory Distress Syndrome (CARDS) toxin in Mycoplasma pneumoniae. Interestingly, recombinant portions of the N-terminal region of LIC10778 protein showed binding to laminin, collagens I and IV, vitronectin and plasma and cell fibronectins using overlay blotting technique, especially regarding the binding site identified by phage display. These data validate our preliminary phage display biopanning and support the predicted three-dimensional models of LIC10778 protein and other members of PF07598 protein family, confirming the identification of the N-terminal cell binding domains that are similar to ricin-like toxins. Moreover, fluorescent fused proteins also confirmed that N-terminal region of LIC10778 is capable of binding to VERO and A549 cell lines, further highlighting its virulence role during host-pathogen interaction in leptospirosis probably mediated by its C-terminal domain. Indeed, recent results in the literature confirmed this assumption by demonstrating the cytotoxicity of a closely related PF07598 member.